2015
DOI: 10.1073/pnas.1514657112
|View full text |Cite
|
Sign up to set email alerts
|

Compromising the phosphodependent regulation of the GABA A R β3 subunit reproduces the core phenotypes of autism spectrum disorders

Abstract: Alterations in the efficacy of neuronal inhibition mediated by GABA A receptors (GABA A Rs) containing β3 subunits are continually implicated in autism spectrum disorders (ASDs). In vitro, the plasma membrane stability of GABA A Rs is potentiated via phosphorylation of serine residues 408 and 409 (S408/9) in the β3 subunit, an effect that is mimicked by their mutation to alanines. To assess if modifications in β3 subunit expression contribute to ASDs, we have created a mouse in which S408/9 have been mutated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…However, in our metabotropic studies only SGE-516 significantly altered sIPSC properties, with an increase in sIPSC amplitude. Our previous data has demonstrated the link between PKC-mediated phosphorylation of β3 subunits with a subsequent reduction in GABA A R endocytosis and an increase in IPSC amplitude (Jovanovic et al, 2004; Kittler et al, 2005; Vien et al, 2015). …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, in our metabotropic studies only SGE-516 significantly altered sIPSC properties, with an increase in sIPSC amplitude. Our previous data has demonstrated the link between PKC-mediated phosphorylation of β3 subunits with a subsequent reduction in GABA A R endocytosis and an increase in IPSC amplitude (Jovanovic et al, 2004; Kittler et al, 2005; Vien et al, 2015). …”
Section: Discussionmentioning
confidence: 93%
“…We have previously shown that the naturally occurring NAS, THDOC, increased tonic current in part through phosphorylation of S408/409 of the β3 subunit (Abramian et al, 2014; Vien et al, 2015). To further our understanding of the NAS-mediated increase in tonic current we measured the effects of ALLO, SGE-516, on the phosphorylation and membrane expression of β3 subunits in hippocampal slices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the basic mechanisms could be related directly to the δ subunit, alterations in associated subunits, such as altered phosphorylation of the β3 subunit, as observed in Fmr1 KO mice (Vien et al, 2015), could also play a role. The possibility of identifying the underlying mechanisms and finding ways to increase surface expression of δ subunit-containing GABA A Rs is particularly intriguing since the current findings indicate that a substantial amount of δ subunit protein is present in the neurons but fails to reach its normal localization at the dendritic surface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when S408/9 of β3 subunits have been mutated to alanines (S408/409A), the increase in α4 PKC-mediated phosphorylation is abolished and THDOC fails to increase the cell surface expression of the α4 subunit (104). …”
Section: Alterations Of Trafficking By Phosphorylationmentioning
confidence: 99%